Pengaruh Dukungan Suami terhadap Istri yang Mengalami Kecemasan pada Kehamilan Trimester Ketiga di Kabupaten Gianyar - Diani, Luh Putu Prema; Susilawati, Luh Kadek Pande Ary (Jurnal Psikologi Udayana, 2013)
The pregnancy period is a period when the body of a pregnant woman experience physical changes and psychological changes caused by pregnancy hormones increase. Hormonal changes experienced by pregnant women will result the changes in emotion and elicits some reaction among others happiness, sensitive, getting sad easily, disappointed, hurt, anxiety and even stress. Under these conditions, the husband’s support needed during pregnancy.It is very important for pregnant women to reduce the level of anxiety,so that pregnant women can live a healthy life. This study aims to determine whether the presence or absence of husband’s support influence against wives who experience anxiety in the third trimester of pregnancy in Gianyar regency. This study used nonprobability sampling with purposive sampling technique. Nonprobability sampling. This research is non-experimental (ex post facto) that consists of two groups: a control group and experimental group consisted of 30 people. Researchers use two scales,husbands support scale and the scale of anxiety in the third trimester pregnant women. Data obtained in this research is processed with independent samples t-test to see the effect of the husband to support his wife who experience anxiety in the third trimester of pregnancy. Analysis Independent samples t-test produces sig. (2-tailed) of 0.000 (p <0,05). Results of this study indicate that there are significant influence between husband’s support against wives who experience anxiety in the third trimester of pregnancy. The group of pregnant women who do not live with her husband has a high-anxiety category. Meanwhile, the group of third-trimester pregnant women living with their husbands has low-medium anxiety category. Keyword : Husband Support, Anxiety, Pregnancy Third Trimester